Desejo por conforto térmico: estratégias adaptativas e modelos de conforto térmico no semiárido paraibano - Sousa, Mayara Cynthia Brasileiro de (2018)
Comfort in a given environment acts directly on the way users use, perceive, and interact with the space, which itself reflects on their own health, productivity and well-being. And so, the during the last few decades indices have been proposed to quantify and qualify conditions that concern desirable thermal comfort for human beings; highlighting two types: those that are based on heat balance, and those that associate comfort with the adaptive strategies. The two models present contrasting theoretical and practical bases, are objects of various comparative studies, and present inconsistencies in their application in the many situations from which such indices have been calculated. Association of such inconsistencies in thermal environments (whether naturally or artificially conditioned), where the respondents had become accustomed was frequent. In this context, this work analyzes the sensations, perceptions and preferences of people with differing thermal histories (being from different regions of the country), yet who were present during the summer and winter of 2017 in the semi-arid region of Paraíba, specifically in the city of Campina Grande. Questionnaires (583) were applied; being grouped as to the naturally ventilated and artificially conditioned environments, while the environmental variables were measured: air temperature, global temperature, relative humidity, and air velocity. Study of physiological adaptation using the Cluster technique supported grouping of cities in accordance with their thermal histories. To achieve thermal comfort, a preference for colder environments was observed in the interviewees, opposing the idea that thermal neutrality is necessary, and corroborating the theory that people move towards cooler environments in hot cities. It was also observed that perception, thermal preference, and cooling method preferences are influenced by the participant’s frequencies of exposure to artificially conditioned environments, and to external spaces. For comfort prediction, the index that obtained the best result was the Predicted Mean Vote, and its extension to hot climates calculated solely to the expectation factor, both in naturally ventilated and artificially conditioned situations, this without regard to the respondent’s contemporary residence. A linear trend line was detected for air temperature and operative temperature of perceived thermal sensations and preferences, however, no trend was observed using SET. People were found in comfort, without environmental control, at operating temperatures higher than 25.5°C, and with air velocity higher than 1m/s, suggesting greater acceptability in leisure environments of higher air speeds.